Soil erosion mapping in the La Mesa watershed using remote sensing and geographic information systems - Nonan, Alan Ceniza (2001)
A major problem faced by land-use planners and decisionn-makers in the past has been the acquisition of accurate and timely information on the magnitude of land deterioration particularly in watershed areas. As a quick and modern approach to Environmental Impact Assessment (EIA), Remote Sensing (RS) and Geographic INformation Systems (GSIS) techniques were used in assessing soil loss in the La Mesa watershed. In this particular study, the modified Universal Soil LOss Equation (MUSLE) was used as a model in estimating the rate of soil loss. Soil erosion in the different portions of the study area was estimated based on the product of the factors of MUSLE; rainfall erosivity (R), soil erodibility (K), length-slope factor (LS), landcover factor (C) and conservation and management practices (P). Thematic map layers were generated by processing and analyzing the input data of the factors of MUSLE. Two (2) sets of multi-temporal, multi-sensor satellite data were analyzed and interpreted using remote sensing software and a landcover map was produced. Likewise, four map layers consisting of R,K,LS and CP values were generated using GIS software by integrating textual or attribute data with spatial or geographic information. Finally, soil erosion maps were generated depicting soil loss in the different areas of the watershed. Total soil loss (in tons per year) and average soil loss (in tons per hectare per year) were estimated for different scenarios of the watershed ranging from eighty five percent (of the total watershed area)forest denudation to complete forest.